Strategi Pembelajaran Menulis Berbasis PAKEM Pada Siswa Kelas IV di MI Azzaroofah Jakarta Timur - Gusti Yarmi (Prosiding Seminar Nasional Jurusan PGSD FIP UNP Tahun 2015, 2015)
The general objective of this research is to gain a deep understanding of how the application of learning writing by applying active learning in MI Azzaroofah Jakarta Timur. The specific objective of this research to know in depth the following matters: (1) learning writing approach in MI Azzaroofah Jakarta Timur; (2) activities in learning writing based active learning in MI Azzaroofah Jakarta Timur. In accordance with the objectives to be achieved, the research method used is a qualitative research method of ethnography. A qualitative approach using ethnographic methods referred to in this research is to explain all aspects of the culture that exists in the application of learning writing based active learning in MI Azzaroofah. Results of this research are: 1) learning writing approach used is PAKEM. Application of PAKEM very prominent visible in terms of student activity, fun approach to teachers and the use of the environment as a learning resource, especially museums 2) The activities carried out in the teaching of writing is to write a real variety of activities, contextual and combined with other activities; 3) specific findings that are uniquely found are the activities in the writing learning is to write a journal, writing news, writing reports from a variety of activities and excursions, combining writing activities with a variety of activities in schools, and take advantage of the museum as primary source of learning